3D printing of ductile equiatomic Fe-Co alloy for soft magnetic applications - Li, Shihao (2022)
The equiatomic Fe-Co alloy is an ideal soft magnetic material due to the combination of high saturation magnetization, permeability and low coercivity it offers. The ordered B2 phase in it, however, makes it highly brittle and hence unsuitable for industrial-scale manufacturing of bulk soft magnets. In this work, we employ the laser powder bed fusion (LPBF) technique—a widely used one for additive manufacturing of metallic parts—to fabricate bulk equiatomic Fe-Co blocks with a microstructure that almost-exclusively contains the disordered body centered cubic (BCC) phase. It plus the high dislocation density (an inherent attribute of the LPBF technique) impart considerable ductility to the as printed alloy, which will make it highly amenable for post-processing mechanical operations such as machining. Subsequent annealing heat treatment (HT) will facilitate disordered BCC to ordered B2 phase transformation and reduction in dislocation density and residual stresses, all of which will maximize the soft magnetic properties. This study demonstrates a viable method to manufacture equiatomic Fe-Co parts with desired geometry and magnetic properties.